Formation and growth behavior of TGO layer in TBCs with HVOF sprayed NiCr bond coat - Parlakyigit, Abdullah Selim; Özkan, Derviş; Oge, Mecit; Ozgurluk, Yasin; Doleker, Kadir Mert; Gulmez, Turgut; Karaoğlanlı, Abdullah Cahit; Özgürlük, Yasin; Karaoğlanlı, Abdullah Cahit; Özkan, Derviş (Ice Publishing, 2020)
In this study, the oxidation behavior of thermal barrier coatings (TBCs) with a nickel-chromium (NiCr) bond coat was investigated under high-temperature atmospheric conditions. Nickel-chromium bond coats were deposited on an Inconel 718 substrate using the high-velocity oxy-fuel (HVOF) spray technique. Production of TBCs was done with deposition of topcoats from yttria-stabilized zirconia using the atmospheric plasma spray technique. After the production of coatings, isothermal oxidation tests were conducted at 900, 1000 and 1100 degrees C in air atmosphere for different time periods up to 50 h. The formation and growth behavior of the thermally grown oxide (TGO) layer and the microstructural evolutions in the TBC system were investigated with scanning electron microscopy and elemental mapping analysis. The results showed that the TGO layer was composed of only chrome oxide at 900 and 1000 degrees C. However, above 1000 degrees C, this layer extremely thickened and mixed oxides formed with the oxidation of nickel in the bond coat composition. The effect of TGO layer development on the ceramic topcoat and the damage potential of the coating system were also evaluated.
Keywords: Coatings; Oxidatio; Thermal Spray